Major depressive disorder-associated SIRT1 locus affects the risk for suicide in women after middle age. (August 2019) - Hirata, Takashi; Otsuka, Ikuo; Okazaki, Satoshi; Mouri, Kentaro; Horai, Tadasu; Boku, Shuken; Takahashi, Motonori; Ueno, Yasuhiro; Sora, Ichiro; Shirakawa, Osamu; Hishimoto, Akitoyo
Highlights: Prior GWAS of female major depressive disorder (MDD) hit SIRT1 SNPs as top candidates. We investigated the effect of MDD-associated SIRT1 SNPs in suicide completers. SIRT1 SNPs were associated with suicide in women aged ≥50 years. SIRT1 gene expression in DLPFC did not differ between suicides and non-suicides. DNAJC12 gene expression in DLPFC was decreased in suicide brains. Abstract: A recent genome-wide association study (GWAS) for major depressive disorder (MDD) in Chinese women identified a single-nucleotide polymorphism (SNP), rs12415800, near the Sirtuin1 ( SIRT1 ) gene as one of the top candidate loci. However, no study has shown a genetic association between SIRT1 and completed suicide, which is one of the most serious outcomes of MDD. In this study, 778 suicide completers and 760 controls in a Japanese population were genotyped for two SNPs in strong linkage disequilibrium (rs12415800 and rs4746720 in 3′UTR). We found significant associations between both SNPs and completed suicide among women aged ≥50 years. Additional analysis using postmortem brain tissues (10 suicide brains and 13 non-suicide brains) revealed the following: while SIRT1 gene expression in the prefrontal cortex did not differ between suicide and non-suicide brains, DNAJC12 gene expression, potentially implicated by the SNPs genotyped here, was significantly decreased in suicide brains ( p  = 0.003). In conclusion, regarding the genetic association of SIRT1 with MDD that was previously identified in women by the Chinese GWAS, we successfully validated our results using a female suicidal cohort in the same Asian population with the same direction of allelic effect.